Structural Insight into the Mechanisms of Targeting and Signaling of Focal Adhesion Kinase - Liu, Gaohua (American Society for Microbiology, 2002)
Focal adhesion kinase (FAK) is a nonreceptor tyrosine kinase whose focal adhesion targeting (FAT) domain interacts with other focal adhesion molecules in integrin-mediated signaling. Localization of activated FAK to focal adhesions is indispensable for its function. Here we describe a solution structure of the FAT domain bound to a peptide derived from paxillin, a FAK-binding partner. The FAT domain is composed of four helices that form a “right-turn” elongated bundle; the globular fold is mainly maintained by hydrophobic interactions. The bound peptide further stabilizes the structure. Certain signaling events such as phosphorylation and molecule interplay may induce opening of the helix bundle. Such conformational change is proposed to precede departure of FAK from focal adhesions, which starts focal adhesion turnover.